2018
DOI: 10.7150/thno.25189
|View full text |Cite
|
Sign up to set email alerts
|

RGS4 deficit in prefrontal cortex contributes to the behaviors related to schizophrenia via system xc--mediated glutamatergic dysfunction in mice

Abstract: Rationale: Although molecular investigations of regulator of G-protein signaling 4 (RGS4) alterations in schizophrenia patients yielded partially inconsistent findings, the previous studies suggested that RGS4 is both a positional and functional candidate gene for schizophrenia and is significantly decreased in the prefrontal cortex. However, the exact role of RGS4 in the pathophysiology of schizophrenia is unclear. Moreover, a whole genome transcription profile study showed the possibility of RGS4-regulated e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
19
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 53 publications
(59 reference statements)
1
19
0
Order By: Relevance
“…The target genes of miR-195 predicted by bioinformatics are highly enriched in signaling pathways associated with neural junctions and synaptic plasticity, and these pathways are involved in the pathogenesis of SZ (Beveridge et al, 2010). Many of the predicted target genes of miR-195, such as RGS4, GRM7, GRIN3A, HTR2A, and PLXNA2, have been reported to correlate with SZ, providing evidence of a post-transcriptional mechanism that underlies SZ-associated glutamatergic and synaptic dysfunction (Huang et al, 2018; Tang et al, 2017; Yu et al, 2018b). For example, Mellios et al showed that miR-195 targets the 3′-untranslated region of BDNF in the human prefrontal cortex (PFC), resulting in downregulation of BDNF protein expression (Mellios et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…The target genes of miR-195 predicted by bioinformatics are highly enriched in signaling pathways associated with neural junctions and synaptic plasticity, and these pathways are involved in the pathogenesis of SZ (Beveridge et al, 2010). Many of the predicted target genes of miR-195, such as RGS4, GRM7, GRIN3A, HTR2A, and PLXNA2, have been reported to correlate with SZ, providing evidence of a post-transcriptional mechanism that underlies SZ-associated glutamatergic and synaptic dysfunction (Huang et al, 2018; Tang et al, 2017; Yu et al, 2018b). For example, Mellios et al showed that miR-195 targets the 3′-untranslated region of BDNF in the human prefrontal cortex (PFC), resulting in downregulation of BDNF protein expression (Mellios et al, 2008).…”
Section: Discussionmentioning
confidence: 99%
“…Thus, the subchronic model of SZ was utilized in this study. Moreover, the dose of MK-801 (0.6 mg/kg/day) was utilized in our previous research (Huang et al, 2018;Ding et al, 2019). Based on the hypothesis of this past study, we evaluated the effects of GPER1 deficiency on the hyperlocomotion, stereotypical behaviors, novel object recognition, social interaction, general activity, spatial learning, and the executive capability of the mouse subchronic model of SZ.…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, RGS4, RGS6, RGS7, and RGS20 can alter behavioral effects of opioids, with RGS4 and RGS20 promoting analgesic activity (28,(43)(44)(45)(46). RGS4, which has extensive distribution in regions of the brain (37,47), is implicated in a number of dopamine-related diseases, including schizophrenia (48,49), and has been a source of questions regarding its role in movement disorders (27,50,51). Driven by these examples of genetically-based observations, and others, small-molecule modulators of RGS protein function have emerged as attractive tools for more closely examining these processes using pharmacological methods.…”
Section: Rgs Proteins In Neurological Processesmentioning
confidence: 99%